2015
DOI: 10.1136/bjophthalmol-2015-307427
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology-specific comparison of long-term outcome of deep anterior lamellar keratoplasty for corneal diseases

Abstract: DALK provides good visual acuity with slight ECD decrease over long term in all groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“… 48 DALK provides good long-term visual outcome for the patients with herpetic keratitis, keratoconus, stromal scars and corneal dystrophies. 49 …”
Section: Resultsmentioning
confidence: 99%
“… 48 DALK provides good long-term visual outcome for the patients with herpetic keratitis, keratoconus, stromal scars and corneal dystrophies. 49 …”
Section: Resultsmentioning
confidence: 99%
“…Its indications have broadened to include not only routine keratoconus, post-infectious leukoma, and stromal dystrophies, but also serious infective keratitis refractory to medical treatment, keratoconic eyes with history of previous hydrops, descemetocele, and keratoglobus. 5,[9][10][11][12][13][14] Several studies report good outcomes of DALK performed in eyes affected by keratoconus with history of corneal hydrops, demonstrating that the presence of a break into the DM is not an absolute contraindication for DALK. 9 Additionally, it has been also demonstrated that intraoperative unexpected DM ruptures may be mended with good results.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is a serious complication after corneal transplantation that can lead to permanent loss of vision. The incidence of glaucoma varies among surgical procedures; for example, it has been calculated to be 9% to 35% after penetrating keratoplasty (PKP), 1 4 0% to 4.5% after anterior lamellar keratoplasty (ALK), 5 7 and 2% to 14% after endothelial keratoplasty (EK). 8 12 The trends of increases in postoperative transient intraocular pressure (IOP) also vary among these procedures: 29% to 80% after PKP, 17% to 36% after ALK, and 31% to 60% after EK.…”
Section: Introductionmentioning
confidence: 99%